Karakterisasi Glukoamilase Hasil Produksi Aspergillus niger BCS dengan Penyangga Fermentasi Sekam dan Dedak - Mahyudin A. Rahman; Koesnandar Koesnandar; Gany H.; Ahmad Marasabessy; Ali Rohman; Usman Sumo FT (Fakultas Farmasi Universitas Pancasila, 2004)
Glucoamylase, the enzyme which converts starch to dextrins and glucose, is used in the starch-processing industry, especially for the production of glucose crystal and high fructose syrup. The aim of this work was to produce glucoamylase by Aspergillus niger BCS using rice husk as solid substrate support. For this purpose, rice husk added to the mixture was optimized on a fixed weight ratio of cassava starch and rice bran. After that, using optimum rice husk concentration, optimization of the weight ratio of cassava starch and rice bran was carried out. Glucoamylase A. niger produced in this work was characterized by determining its optimum pH and temperature, its stability under various pH and temperature, its kinetic parameters, its hydrolysis products using soluble starch as substrate, and its molecular weights. The optimum conditions for glucoamylase production by A. niger obtained when the weight ratio of cassava starch: rice bran was 1:1 (dry basis, db) and the rice husk concentration in the fermentation medium was 20% by weight (db). Under these optimized conditions, enzyme units as high as 1774 U/g dry fermented substrate was obtained when fermentation was carried out for 5 days at 30°C. Optimum pH of glucoamylase A. niger was 4.5 and its optimum temperature activity was 65°C. This enzyme was stable at pH 3.0 - 7.0 and at a temperature up to 50°C.